Analysis of Student Satisfaction Levels with Computer Laboratory Services with a Fuzzy Service Quality Approach - Diana, Elviza; Kurniah, Reni (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
Quality of education provided Prof. University DR. Hazairin, SH Bengkulu, is a higher education institution that is committed to providing the best service to its students, including computer laboratory services. Computer laboratory services have an important role in supporting student learning and research, therefore, it is important to measure and analyze the level of student satisfaction with this service. In measuring the level of student satisfaction with computer laboratory services using the Fuzzy Service Quality approach method. This approach allows us to understand the complexity and diversity of students' views on service quality, which are often difficult to measure with conventional approaches. By using the Fuzzy Service Quality model, we can describe the level of student satisfaction more accurately, identify areas that need improvement, and increase the effectiveness and efficiency of computer laboratory services. Based on the research results, it was concluded that all aspects had a score above 3, which means student satisfaction with computer laboratory services has been met well. The highest score from all aspects is the cool and comfortable computer laboratory room and the lowest is 3.90 while the lowest is 2.77 for the Computer Laboratory service providing academic information and non-academic services in the form of a website (online). The reliability aspect (reliability of lecturers, and academic staff) has the highest reliable value of 0.916. Based on the results of Servqual and Logical Fuzzy data analysis, a high GAP value was found in students' perceptions and expectations regarding computer laboratory services providing academic information and non-academic services in the form of websites (online).